In Their Right Minds: The Lives and Shared Practices of Poetic Geniuses by Carol Brooks Platt - Grosso, Michael (Journal of Scientific Exploration, 2015)
The author introduces her remarkable book with this remark: “My interest in the voices and visions of poets and prophets was precipitated by a dear friend’s claim to channel angels after her mother died.” How was it possible for her friend to undergo such a substantial change in her sense of reality? How could she accept angelic encounters as really real? Witnessing this transformation galvanized Carole Brooks Platt to do twenty years of research, the present book resulting. The book indeed contains a wealth of densely packed ideas, data and references, drawn from diverse sources and disciplines. Impossible to cover so much in a brief review, I will say something about the main points. The question Platt poses is a large one. What kind of world do we inhabit? What is it like to be a human being? Do poets, prophets, mediums, and others break out of their material shells and reach into other dimensions of reality or is all that illusion, self-deception, escapism? This is a great metaphysical as well as an intensely personal question of our time. Although typically not discussed in the major news media, the issues it entails lurk in the background of all that we think and do.